Shaking Table Test On Seisemic Response Behavoir Of 2-Story Masonry House Model With Pp-Band Mesh Retrofitting - Sathiparan, N.; Sakurai, K.; Numada, M.; Meguro, K. (My University, 2011)
This report is the study on the dynamic properties and seismic performance of the two-story masonry house model by the 1/4-scale shaking table test. The specimen is an ordinary dwelling house in south Asia. The shaking table test was carried out by the sinusoid input wave of the one direction in the horizontal direction. Acceleration and displacement are measured. The dynamic response properties and comparative study of one-direction excitation were explained.
Keywords: two-story masonry; polypropylene band